Molecular mechanism of hepcidin deficiency in a patient with juvenile hemochromatosis - Alexandra Rideau; Bastien Mangeat; Thomas Matthes; Didier Trono; Photis Beris (Haematologica, 2007)
We describe a point mutation creating an additional ATG codon in the 5′ untranslated region (UTR) of the HAMP gene, in a patient with juvenile hemochromatosis. By transient in vitro transfection studies, we provide evidence that the additional ATG is functional and prevents normal hepcidin production by inducing an aberrant translation initiation of the pre-hepcidin mRNA.